Dot and the Kangaroo - Ethel C. Pedley
A young girl named Dot finds herslf lost while playing in the woods. Not knowing how to find her way home, she becomes lonely and afraid. Just as Dot is beginning to believe that she'll never see her mother and father again, she meets a friendly kangaroo who comforts her and helps her through the deep woods. Join Dot and the Kangaroo as they embark on an exciting adventure through the Australian outback!